A guide to polarized airway epithelial models for studies of host–pathogen interactions. (2nd July 2018) - Hasan, Shakir; Sebo, Peter; Osicka, Radim
Abstract : Mammalian lungs are organs exhibiting the cellular and spatial complexity required for gas exchange to support life. The respiratory epithelium internally lining the airways is susceptible to infections due to constant exposure to inhaled microbes. Biomedical research into respiratory bacterial infections in humans has been mostly carried out using small mammalian animal models or two‐dimensional, submerged cultures of undifferentiated epithelial cells. These experimental model systems have considerable limitations due to host specificity of bacterial pathogens and lack of cellular and morphological complexity. This review describes the in vitro differentiated and polarized airway epithelial cells of human origin that are used as a model to study respiratory bacterial infections. Overall, these models recapitulate key aspects of the complexity observed in vivo and can help in elucidating the molecular details of disease processes observed during respiratory bacterial infections. Abstract : Respiratory bacterial infections in humans cause considerable mortality and morbidity. During infection, the coordinated action of bacterial virulence factors disrupts epithelial cell homeostasis and function. The effects of infection on epithelial cell function, such as ciliary beating, polarized secretion responses, barrier function, etc., can be efficiently studied using in vitro polarized airway epithelial cells.